The use of submicron/nanoscale PLGA implants to deliver paclitaxel with enhanced pharmacokinetics and therapeutic efficacy in intracranial glioblastoma in mice - Ranganath, S.H. (2014)
10.1016/j.biomaterials.2010.03.002